2014
DOI: 10.1186/1756-3305-7-145
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of a multi-epitope DNA vaccine via intranasal, peroral, and intramuscular delivery against lethal Toxoplasma gondii infection in mice

Abstract: BackgroundToxoplasmosis is an important zoonosis, being a cause of congenital disease and abortion in animals and humans. DNA vaccination as a promising vaccine remains a challenge for an improved delivery system.MethodsIn this study, attenuated Salmonella typhimurium BRD509 was used to deliver a DNA vaccine encoding several epitopes, derived from the tachyzoite proteins SAG1, GRA1, ROP2, GRA4 and bradyzoite proteins SAG2C, SAG2X of Toxoplasma gondii and A2/B subunit of cholera toxin. The recombinant plasmids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…This novel delivery system has proven successful in inducing protective immunity against many infections such as Toxoplasma gondii [7], Giardia lamblia [8] and Trypanosoma cruzi [9]. In our previous study, attenuated Salmonella typhimurium was used to orally deliver a DNA vaccine of Ts 87, an excretory/secretory antigen from T .…”
Section: Introductionmentioning
confidence: 99%
“…This novel delivery system has proven successful in inducing protective immunity against many infections such as Toxoplasma gondii [7], Giardia lamblia [8] and Trypanosoma cruzi [9]. In our previous study, attenuated Salmonella typhimurium was used to orally deliver a DNA vaccine of Ts 87, an excretory/secretory antigen from T .…”
Section: Introductionmentioning
confidence: 99%
“…These properties make it an attractive antigen for diagnostics and vaccine development [12]. Having excellent immune features, recombinant SAG1 has been the most studied antigen of Toxoplasma for development of antibody-based serological tests and vaccine [32][33][34]. A previous study by Letillois and collaborators showed that rSAG-1 may be used as a marker of reactivated toxoplasmosis in HIV infected patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, significant increase in the cellular and humoral immunity was generated when the mice was immunized with a multi-epitope vaccine containing two T cell epitopes and one B cell epitope of SAG1, GRA1, and GRA4. In addition, vaccinated mice obtained long-term survival rates compared with the unvaccinated controls [12].…”
Section: Epitope-based Vaccine Against Toxoplasmosismentioning
confidence: 99%
“…Intensive efforts and significant advances toward acquiring an effective vaccine are under way to control infection and limit the incidence of the disease; however, no vaccine has, thus, far been available for use in humans [11][12][13]. Currently, the live attenuated tachyzoites of the strain S48 (commercially named "Toxovax") is the only approved vaccine for veterinary use.…”
Section: Introductionmentioning
confidence: 99%